2007
DOI: 10.1002/pola.21977
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polymeric core–shell particles using surface‐initiated living free‐radical polymerization

Abstract: An easy and novel approach to the synthesis of functionalized nanostructured polymeric particles is reported. The surfactant‐free emulsion polymerization of methyl methacrylate in the presence of the crosslinking reagent 2‐ethyl‐2‐(hydroxy methyl)‐1,3‐propanediol trimethacrylate was used to in situ crosslink colloid micelles to produce stable, crosslinked polymeric particles (diameter size ∼ 100–300 nm). A functionalized methacrylate monomer, 2‐methacryloxyethyl‐2′‐bromoisobutyrate, containing a dormant atom t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…37,38 When using the particles from conventional radical polymerization, the initiators have to be further introduced to the surface, [39][40][41][42] while this step can be avoided when using particles prepared directly by ATRP.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 When using the particles from conventional radical polymerization, the initiators have to be further introduced to the surface, [39][40][41][42] while this step can be avoided when using particles prepared directly by ATRP.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] The growing range and specificity of applications are connected to successes in preparing polymeric particles with diverse chemical compositions, morphologies and functions. 19,24,25 Fortunately, these drawbacks can be overcome by the introduction of the burgeoning controlled/living radical polymerization (CLRP) methods, such as nitroxide-mediated polymerization(NMP), [15][16][17][18] atom transfer radical polymerization (ATRP) [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and reversible addition-fragmentation chain transfer polymerization (RAFT). [4][5][6][7][8] Among the diversified techniques for preparing core-shell polymeric particles, a most common and versatile route is to graft polymer brushes by surface-initiated radical polymerization from pre-synthesized particles that bear initiator sites.…”
Section: Introductionmentioning
confidence: 99%
“…This method suffers from ununiform grafted chain lengths and the inevitable formation of free ungrafted chains when conventional radical polymerization is utilized. Jhaveri et al 26 demonstrated the versatility of surface-initiated ATRP by generating a number of different polymeric shell/ poly(methyl methacrylate) core particles and judging from scanning electron microscope observations, they thought that there was no free polymer grown in solution. [35][36][37][38][39][40][41][42][43][44] Surface-initiated CLRP makes it possible to achieve deliberate control over grafted chain length, shell thickness and structrual uniformity as well as the elimination of free homopolymer formation in the synthesis of core-shell particles.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer particles are an effective tool to improve surface property [4,5]. An ideal encapsulation regime should allow the facile adjustment of shell thickness, mechanical strength, and surface potential [6][7][8][9]. The best facile method for the synthesis of the ideal encapsulated polymer particles is the grafting-from approach, where the hyperbranched photoinitiators are attached to the colloidal particles, and then linear chains are grown from the surface to give the covalently attached brush chains using the photo-induced atom transfer radical polymerization [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%